Development engineering meets development studies. Issue 10 (3rd October 2017) - Robbins, Peter; Watkins, Andrew; Wield, David; Wilson, Gordon
Abstract: The importance of science in development has been increasingly recognised in development discourses and policy since 2000. Engineering is less visible though engineering and engineers are important for the building and maintenance of transport, water, energy, industrial, informatics, urban and health systems. This article aims to investigate why engineering has not received more emphasis, including why development engineering has not been institutionalised like tropical medicine. It explores the nature of engineering in development, highlights recent efforts to headline engineering for development and, using analyses of what engineers know and do inside international development, suggests that its profile and effectiveness is emerging.